2016
DOI: 10.1021/acs.joc.6b00308
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Substituted Benzenes via Pd-Catalyzed Cross-Coupling/Cyclization Reaction of Vinyl Halides and Terminal Alkynes

Abstract: A tandem Sonogashira coupling/cyclization/aromatization sequence of β-halo vinyl sulfones/ketones with terminal alkynes has been developed for the construction of benzene rings. Polysubstituted functionalized benzenes containing a sulfonyl or an acyl group could be obtained in up to 95% yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…9,[27][28][29][30] To the best of our knowledge, the coupling reaction between simple alkenyl ligands and external alkynes has been unexplored heretofore. On the other hand, the coupling of alkynes with alkenyl molecules is of ultimate relevance in metal-mediated organic synthesis, [31][32][33][34][35][36] and the alkyne insertion into metal-alkenyl bonds constitutes a key step of the important Dötz reaction. [37][38][39] We selected the diruthenium complex [Ru 2 Cp 2 (CO) 2 (μ-CO) {μ-η 1 :η 2 -C(Ph)vCH(Ph)}]BF 4 , [1]BF 4 , as a convenient starting material to provide a chance for the μ-alkenyl-alkyne coupling; Knox and co-workers previously demonstrated that complexes homologous to [1]BF 4 , bearing different alkenyl substituents, display a versatile chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[27][28][29][30] To the best of our knowledge, the coupling reaction between simple alkenyl ligands and external alkynes has been unexplored heretofore. On the other hand, the coupling of alkynes with alkenyl molecules is of ultimate relevance in metal-mediated organic synthesis, [31][32][33][34][35][36] and the alkyne insertion into metal-alkenyl bonds constitutes a key step of the important Dötz reaction. [37][38][39] We selected the diruthenium complex [Ru 2 Cp 2 (CO) 2 (μ-CO) {μ-η 1 :η 2 -C(Ph)vCH(Ph)}]BF 4 , [1]BF 4 , as a convenient starting material to provide a chance for the μ-alkenyl-alkyne coupling; Knox and co-workers previously demonstrated that complexes homologous to [1]BF 4 , bearing different alkenyl substituents, display a versatile chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…9,27–30 To the best of our knowledge, the coupling reaction between simple alkenyl ligands and external alkynes has been unexplored heretofore. On the other hand, the coupling of alkynes with alkenyl molecules is of ultimate relevance in metal-mediated organic synthesis, 31–36 and the alkyne insertion into metal–alkenyl bonds constitutes a key step of the important Dötz reaction. 37–39…”
Section: Introductionmentioning
confidence: 99%
“…Considering that vinyl halides have been extensively used in organic synthesis, such as in Sonogashira couplings, Nozaki–Hiyama–Kishi reactions, and Kumada couplings, the addition of the vinyl anion derived from vinyl iodide 7 to benzaldehyde 8 could generate the bis-chromene 9 (Scheme ). Indeed, some examples of vinyl iodides being used in the total syntheses of natural products for the preparation of unsaturated ketones have been disclosed .…”
mentioning
confidence: 99%